INVESTIGATING ENGLISH TEACHERS STRATEGIES IN IMPLEMENTING INQUIRY-BASED LEARNING METHODS UNDER THE INTERNATIONAL BACCALAUREATE (IB) CURRICULUM - Sari, Kartika Puspita; Daniel Ari Widhiatama (Journal of Innovation Research and Knowledge, 2024)
This study aims to analyze the implementation of Inquiry-Based Learning (IBL) strategies in elementary English classes within the context of the International Baccalaureate (IB) curriculum at Yogyakarta Independent School (YIS). The research highlights the urgency of transitioning from traditional teacher-centered approaches to student-centered learning models. Through a qualitative approach, this study identifies various challenges and opportunities faced by teachers in implementing IBL, as well as evaluates the effectiveness of this method in creating a more dynamic and participatory learning environment. The findings provide strategic insights for enhancing teacher readiness and developing strategies that schools can adopt to optimize the implementation of IBL, with the ultimate goal of fostering a more transformative and meaningful educational experience for students.